Description and Level of Difficulty in Learning Hematology for Medical Laboratory Technology (MLT) Students during One Year of the COVID-19 Pandemic - Andriani Tri Susilowati; Erma Lestari (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
This research aims (1) to determine the description of learning difficulties and the percentage of supporting and inhibiting factors for learning hematology in the COVID-19 pandemic era, (2) to determine the success rate of learning hematology in the COVID-19 pandemic era. This research is a qualitative descriptive type, with research subjects from D4 Analyst students at the Universitas Muhammadiyah Semarang who study hematology. This data collection was carried out from February to March 2021. Data were collected from a questionnaire via Google Form. Based on the results of the study, the following findings were obtained: 1) description and percentage of supporting and inhibiting factors for hematology learning difficulties as follows: (1) health factors (53.33%), (2) cognitive factors (60%), (3) interest factors (50%). The average internal factor of hematology learning difficulties is 54,44% in the medium category. While the percentage of external factors of learning difficulties in hematology are as follows: (1) family factors (46.67%), (2) living place conditions (46.67%), (3) facilities (48.89%), (4) learning materials (54%). The average external factor of hematology learning difficulties is 49.06% in the medium category, 2) the success rate of learning hematology in the COVID-19 pandemic era with an average of 61.73 (medium). The study results can contribute in the form of information on the description of the factors of learning difficulties in the Hematology course in the COVID-19 pandemic era as a basis for finding solutions.